APLIKASI ANTRIAN DAN PENGOLAHAN DATA BALITA BERBASIS WEBSITE (STUDI KASUS : POSYANDU ARUM DALU DESA SANGGRAHAN) - Christian, Andhika Novia Sandy; Winarsih, SM Santi (STMIK Sinar Nusantara, 2024)
Posyandu activities in Sanggrahan Village have been running smoothly and still use the Posyandu Information System (SIP) book as a guideline for implementing activities. The purpose of this study is to build a web-based application to manage information at Posyandu Arum Dalu Sanggrahan Village. In the web-based application, the author also added a queue number so that the time for implementing posyandu activities could be neatly and better arranged. The author hopes that this web-based application can help the performance and facilitate Midwives and Health Cadres of Sanggrahan Village in terms of processing toddler data.Keywords : Posyandu, Information System, Queue Number